2021
DOI: 10.5735/086.058.0403
|View full text |Cite
|
Sign up to set email alerts
|

Vendace (Coregonus albula) Disperse Their Eggs Widely during Spawning

Abstract: Depending on their reproductive strategy, different fish species either aggregate or disperse eggs and larvae in their reproductive habitat. Because yolk-sac larvae of vendace (Coregonus albula) disperse widely across the littoral and pelagic zones of boreal lakes, it is unclear where the exact spawning and egg incubation locations are. Vendace egg and larvae densities were studied in Lake Southern Konnevesi to clarify its spawning strategy. In autumn 2019, 1-2 weeks prior to spawning, 500 egg samplers were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For example, reductions in prey abundance have been attributed to growth declines in Lake Whitefish within the Laurentian Great Lakes due to the establishment of invasive dreissenid muscles (Pothoven et al 2001;Nalepa et al 2005;Hoyle et al 2011). However, additional studies have reported negative correlations between cohort strength and growth, suggesting that densitydependent competition for limited food resources acts as a growth-regulating mechanism for coregonids (Freeberg et al 1990;Karjalainen 1992;Kratzer et al 2007a), a result further supported by studies in experimental lakes (Healy 1980;Mills et al 1995). Yet still, environmental conditions are believed to influence spawning and hatching success (Freeberg et al 1990;Brown et al 1993;Kratzer et al 2007b), while water temperature, specifically, has been shown to influence growth in laboratory studies (Edsall 1999;Szczepkowski et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…For example, reductions in prey abundance have been attributed to growth declines in Lake Whitefish within the Laurentian Great Lakes due to the establishment of invasive dreissenid muscles (Pothoven et al 2001;Nalepa et al 2005;Hoyle et al 2011). However, additional studies have reported negative correlations between cohort strength and growth, suggesting that densitydependent competition for limited food resources acts as a growth-regulating mechanism for coregonids (Freeberg et al 1990;Karjalainen 1992;Kratzer et al 2007a), a result further supported by studies in experimental lakes (Healy 1980;Mills et al 1995). Yet still, environmental conditions are believed to influence spawning and hatching success (Freeberg et al 1990;Brown et al 1993;Kratzer et al 2007b), while water temperature, specifically, has been shown to influence growth in laboratory studies (Edsall 1999;Szczepkowski et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…However, more understanding of the effect of sex ratio on reproduction rate can be obtained from laboratory experiments (Rowe et al 2004). Recently, we have also succeeded in sampling spawned Vendace eggs from the spawning sites (Karjalainen et al 2021), which enables the estimation of the fertilization rate in situ and the comparison of fertilization rates under different spawner densities and sex ratios in different years.…”
Section: F I G U R Ementioning
confidence: 99%
“…No sexual dimorphism, such as differences in size at age (e.g., data by Järvi 1919Järvi , 1920Järvi , 1942aViljanen 1986) or age at maturity or any secondary sexual characteristics, has been detected in Vendace. Despite being a pelagic schooling species for most of the year, Vendace spawn in pairs (Karjalainen and Marjomäki 2018) in the littoral-sublittoral zone from a depth of a few meters to more than 10 m (Heikkilä et al 2006;Karjalainen et al 2021). Spawning takes place in late autumn in the dark.…”
Section: Introductionmentioning
confidence: 99%
“…Most coregonines spawn nearshore in late-autumn, embryos incubate under ice, and hatch in spring near ice-out, when rising spring water temperatures trigger hatching (Karjalainen et al, 2021(Karjalainen et al, , 2019(Karjalainen et al, , 2015Stockwell et al, 2009). Increases in air temperature and water temperatures of seasonally ice-covered lakes are projected to be greatest during the winter and spring, respectively, in response to climate change (Christensen et al, 2007;Ozersky et al, 2021;Schindler et al, 1990;Winslow et al, 2017).…”
Section: Introductionmentioning
confidence: 99%